Literasi informasi mitigasi bencana banjir terhadap kesiapsiagaan bencana masyarakat di desa bulubonggu kecamatan dapurang - Samsul; Widyastuti; Ismail; Novarita, Amalia; Nisa', Zumrotin (Department Geography Education Faculty of Social Science - Universitas Negeri Jakarta, 2023)
Bulubonggu Village is one of the villages that is often affected by floods, this is proven in 2020 the flood height reached an average of 1-2 m. The village is close to the watershed and has a flat land topography. This flood disaster caused several people's houses and agricultural land to fail crops. This happened due to the lack of understanding of disaster information literacy by the people of Bulubonggu village. This research uses qualitative methods with a spatial approach. The research subject of the Bulubonggu village community. Data collection techniques and instruments are carried out through observation, and interviews. Qualitative descriptive data analysis techniques. The results are a total of 29 people or 36.25% of understanding of disaster information literacy in the Bulubonggu village community was in the medium category, a total of 32 people or 40% had an understanding of disaster information literacy in the community in the low category, and a number of 35 people or 43.75% had an understanding of disaster information literacy in the very low category in the Bulubonggu village community